Model Latihan Shooting Sepak Bola melalui Permainan untuk Usia 13-15 Tahun - Taufik Hidayat Suharto; Ira Arini; Dedi Aryadi; Ridwan Sudirman; Ayi Rahmat; Mukhtar Ridwan (Departement of Mathematics Education, 2024)
This research is motivated by many things that need to be considered before a coach determines a training method for a sport, especially football. On the other hand, as for the problems that are often faced in the field, based on experience, many parents of athletes have the paradigm that their children must become champions in every competition they participate in without understanding the process their children have to go through. The aim of this research and development is to produce a shooting training model for soccer through games for 13-15 year olds. Apart from that, this research and development was carried out to obtain in-depth information about: the development and application of shooting models in soccer through games for ages 13-15 years and to determine the effectiveness, efficiency and attractiveness of children towards the models created. The method used in this research is a qualitative and quantitative approach, which is an approach with the aim of finding answers to problems through the formulation of problems that have been formulated. Based on the data obtained, from the results of the research which consisted of expert validation, small group trials and large group trials as well as discussion of the research results, the researcher can draw the conclusion that (1) the model of shooting training in soccer through the playing method for ages 13 -15 years can be developed. (2) Shooting training model in soccer using the playing method that has been developed, obtained data on the effectiveness and results of the training model for ages 13-15 years.